2014
DOI: 10.1016/j.landurbplan.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Urban planning and sustainable adaptation to sea-level rise

Abstract: Sea-level rise poses major challenges to coastal land uses, and therefore to urban planning processes. In theory, if done well, urban planning can lead to responses to sea-level rise that are socially and environmentally sustainable. In practice, urban planning processes may fall short of this ideal. We use multiple methods to describe and analyse how urban planning processes have led to adaptation to sealevel rise in Lakes Entrance in Victoria, Australia. Adaptation has principally taken the form of restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 40 publications
0
45
0
5
Order By: Relevance
“…This means that defining successful adaptation is more about the sustainability of processes and the principles of fairness and equity than it is about measuring outcomes at any given point in time (Stafford-Smith et al 2011, Hurlimann et al 2014). Successful adaptation is therefore a matter of "socially and environmentally sustainable development pathways, including both social justice and environmental integrity" (Eriksen et al 2011:8).…”
Section: The Interplay Between Barriers and Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that defining successful adaptation is more about the sustainability of processes and the principles of fairness and equity than it is about measuring outcomes at any given point in time (Stafford-Smith et al 2011, Hurlimann et al 2014). Successful adaptation is therefore a matter of "socially and environmentally sustainable development pathways, including both social justice and environmental integrity" (Eriksen et al 2011:8).…”
Section: The Interplay Between Barriers and Limitsmentioning
confidence: 99%
“…Within Australia, there has been a good deal of research on barriers to adaptation to sealevel rise in primary industries and local governments. Commonly identified barriers include a lack of or inconsistent leadership, insufficient knowledge of risks and responses, inadequate http://www.ecologyandsociety.org/vol20/iss3/art5/ funding, difficulties in negotiating among competing values and goals, a lack of institutional support, and poor coordination across levels of government (McDonald 2007, Measham et al 2011, Scally and Wescott 2011, Macintosh 2012, Mukheiber et al 2013, Raymond and Robinson 2013, Hodgkinson et al 2014, Hurlimann et al 2014, Macintosh et al 2014, Marshall and Stokes 2014a. A recent analysis of 79 submissions from industry, government, and civil society organizations to a national inquiry on barriers to climate change adaptation also concluded that governance and tensions around competing policy priorities were seen by most actors to be the major barrier to adaptation (Waters et al 2014).…”
Section: The Interplay Between Barriers and Limitsmentioning
confidence: 99%
“…Spatial planning has been used as a facilitator of adaptation to climate change, but only a limited number of studies have analysed such examples. These studies have found various degrees of success in achieving sustainable or successful adaptation [129][130][131][132][133]. While research has begun to link spatial planning, climate change and water, the focus has predominantly been on flood mitigation and control, rather than urban water supply management [102,134,135].…”
Section: Spatial Planning Sustainable Urban Water Management and CLImentioning
confidence: 99%
“…Moreover, they suggest that planning can offer the continuity and consistency required in adaptation planning despite possible political or cultural changes-an important factor given the many studies (e.g., [142]) which show that loss of knowledge can be a major problem in sustaining climate change adaptive capacity. Indeed, spatial planning has been the catalyst for many adaptation actions [130,142]. This paper argues that the need to adapt to a changing climate will necessarily change the relationship between the disciplines of spatial planning and urban water supply management.…”
Section: Spatial Planning Sustainable Urban Water Management and CLImentioning
confidence: 99%
“…Researchers working in conjunction with residents in participatory action research and using new technologies such as mobile applications can improve understanding of problems and solutions while building collective efficacy and knowledge to address current and future environmental challenges within the built environment (Evers et al , 2016). Successful participatory projects may increase knowledge for both residents and experts working in hazard-prone areas (Berke et al , 2011), yet hazard risk assessments and urban planning for hazard impacts frequently operate within expertise-driven groups lacking significant community engagement (Archer et al , 2014; Godschalk et al , 2003; Horney et al , 2013; Horney et al , 2015; Hurlimann et al 2014). …”
Section: Introductionmentioning
confidence: 99%